Using Automatic Satellite Images and Monitoring of Water Objects (Journal of University of Babylon for Engineering Sciences, 2018)
The satellite radar survey and monitoring system for the mapping of water bodies in Slovenia and its border states was carried out by satellite radars (Sentinel-1). Algorithms automatically detect new archived data, retrieve and analyze data, and publish and transmit results to a website. New surveys were available every six days, but this time the time will be halved, when Sentinel-1 starts sending data.